ANALISIS PEMANGKU KEPENTINGAN DALAM TRANSFORMASI KEBIJAKAN FISKAL HIJAU - Fitri Nurfatriani; Dudung Darusman; Dodik Ridho Nurrochmat; Ahmad Erani Yustika (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
The current fiscal policy in the forestry sector is still dominated by the management of timber extraction as a basic for sharing forestry revenues from central to local government. Therefore, it requires some shift towards green fiscal policies which positioning the overall benefitsof forests. In order to prepareon green fiscal policyframework, it is required the analysisof stakeholders involved in the formulation of green fiscal policy. The objectives of the research are to identify, categorize and investigate the relationship among the involved stakeholders at national and sub-national levels, and then to formulate green fiscal policy by using stakeholders analysis method. The analysis results show that there are 18 involved stakeholders consistsof five key stakeholders, seven primary stakeholders and six secondary stakeholders. Based on the categoryof stakeholders involved in the formulation of green fiscal policy as key players, context setters, subjects and crowds, it is realized the great need for strategies to optimize stakeholders management by enhancing colaboration and cooperation between the subjects and the key players. This will be better achieved by increasing effective cooperation and collaboration between central and localgovernmentsin implementingthecurrent fiscal policyon forestry.